Richness and biogeography of Pteridoflora in montane forests of eastern Mexico - J. Daniel Tejero-Díez; Perla V. Rodríguez-Sánchez; Raúl Contreras-Medina; Julio Cesar Ramírez-Martínez; Jonathan D. Amith; Leccinum J. García-Morales; Celia Sanginés-Franco; Isolda Luna-Vega (PLoS ONE, 2026)
This study compiles and updates the checklist of ferns and lycophytes from the Sierra Madre Oriental (SMOR), Mexico. We analyzed the distribution and richness of these groups of seedless vascular plants to ensure the accuracy and reliability of the data. We reviewed information on these taxa from regional floristic studies, field explorations, and herbarium specimens. Our updated list includes 567 species, of which 511 are ferns and 56 lycophytes, organized into 37 families and 137 genera. The five most species-rich families are Pteridaceae (131), Polypodiaceae (76), Dryopteridaceae (68), Aspleniaceae (45), and Selaginellaceae (41). The five most species-rich genera are Asplenium (42), Elaphoglossum (30), Pleopeltis (24), Myriopteris (22), and Selaginella (21). The Mexican states with the greatest species richness within the SMOR are Puebla (423), Hidalgo (322), Querétaro (227), and Tamaulipas (181). The five grid cells with the highest richness, each containing more than 190 species, are situated in the southern part of the SMOR (Puebla and adjacent parts of Veracruz). The physiographic provinces with the greatest diversity are Carso Huasteco and the Gran Sierra Plegada, with 523 and 175 species, respectively. Latitudinal analysis indicated low richness at the northern extreme (28 °- 29 ° N, 11 species) and high richness at the southern extreme (19 °- 20 ° N, 469 species), with a notable peak at 24 °- 25 ° N (350 species). The highest diversity within elevation intervals occurs at 1,000–1,500 m (455 species). The SMOR contains 22 species of the pteridoflora classified under various risk categories according to the Mexican Official Norm NOM-059-SEMARNAT-2010, including seven listed on the IUCN Red List and ten protected under CITES. The taxonomic diversity index shows that the SMOR is among Mexico’s most species-rich mountain ranges. The species richness documented here in the SMOR accounts for 50–54% of the pteridophyte diversity recorded in Mexico, increasing to 59.3% based on recent floristic studies conducted in the region.